Comparison of topical estrogen and platelet-rich plasma injections in the treatment of postmenopausal vaginal atrophy - Atlihan, Ufuk; Ata, Can; Yavuz, Onur; Avsar, Huseyin Aytug; Erkilinc, Selcuk; Bildaci, Tevfik Berk (Frontiers in Medicine, 2025)
BackgroundPlatelet-rich plasma (PRP) is considered safe and is a low-cost, simple, natural, and minimally invasive method for vaginal rejuvenation. We aimed to compare the effects of hormonal treatment options and PRP use for postmenopausal vulvovaginal atrophy (VVA).MethodsFrom a total of 66 patients, topical estrogen treatment was administered to 36 patients, and PRP treatment was used on 30 patients who had previously received topical estrogen treatment without obtaining a response. To assess the impact of VVA and associated symptoms on the quality of life of patients, three different questionnaires, namely the Vaginal Health Index (VHI), Female Sexual Function Index (FSFI), and the Vulvovaginal Symptoms Questionnaire (VSQ), along with a Visual Analog Scale (VAS), were administered at 4-week intervals.ResultsIn the assessment at the 12th week, the FSFI and VSQ results obtained in patients treated with PRP showed a significant difference compared with those treated with topical estrogen (p = 0.004 and p < 0.001, respectively).ConclusionPRP injections are a safe and effective minimally invasive monotherapy for postmenopausal VVA and, consequently, vulvovaginal rejuvenation. PRP injections are regarded as a promising method for the treatment of VVA in postmenopausal patients with contraindications to hormone therapy and improving hydration of the vaginal mucosa.